Answer:
1
Step-by-step explanation:
Eliminate parentheses using the distributive property.
= -4i +1/4 -5i +3/4 -8i +17i
= (1/4 +3/4) +i(-4 -5 -8 +17)
= 1 + 0i
= 1
Multiply x to (-y) then x to (z)
mean x(-y)+ x(z)
plug in the variable given
(-1)(-(-2)+5)
-2-5=-7
Try to imagine this word problem, there is a wall and a ladder leaning against it, the space from the bottom of the ladder is labeled 6 and the length of the height the ladder reaches on the wall is 8. Imagine this as a right triangle now, where the length of the ladder is the hypotenuse and the length of the legs of the triangle is 6 and 8. Because we know this, we can use the Pythagorean theorem, a^2+b^2=c^2
We then plug in the values and you get 6^2+8^2=c^2
When you simplify, you get 36+64=c^2 which is c^2=100
When you solve for c, you get c=10 which would be the length of the ladder :)
hope this is ans . Brother